A 9-Valent HPV Vaccine Against Infection and Intraepithelial Neoplasia in Women. Issue 7 (July 2015) - Joura, Elmar A.; Giuliano, Anna R.; Iversen, Ole-Erik; Bouchard, Celine; Mao, Constance; Mehlsen, Jesper; Moreira, Edson D.; Ngan, Yuen; Petersen, Lone Kjeld; Lazcano-Ponce, Eduardo; Pitisuttithum, Punnee; Restrepo, Jaime Alberto; et al.
Abstract : ABSTRACT: Almost all premalignant and malignant lesions of the cervix occur in women infected with the human papillomavirus (HPV). Vaccination with HPV prevents infection and disease caused by several oncogenic HPV types. Current HPV vaccines prevent approximately 70% of cervical cancers through protection from HPV-16 and HPV-18. The investigational 9-valent (9vHPV) viruslike particle vaccine contains the 4 HPV types present in the quadrivalent HPV (qHPV) vaccine (types 6, 11, 16, and 18) plus 5 additional oncogenic types (31, 33, 45, 52, and 58). Increased coverage provided by this new vaccine offers the potential to increase overall prevention of cervical cancer to approximately 90%. This randomized, international, multicenter, double-blind study compared the efficacy and immunogenicity of the 9vHPV vaccine and the qHPV vaccine in women 16 to 26 years of age. The efficacy portion of the study included 14, 215 women who underwent randomization. Both vaccines were administered in a series of 3 intramuscular injections on day 1 and at months 2 and 6. An inactive placebo was not used for ethical reasons. Swabs collected from labial, vulvar, perineal, perianal, endocervical, and ectocervical tissue were used for HPV DNA testing. Liquid-based cytologic testing (Pap testing) was performed regularly. Participants with an abnormal Pap test result were referred for colposcopy; the affected tissue was tested for HPV. Modified intention-to-treat efficacy analyses included participants with and without prevalent infection or disease. The incidence of high-grade cervical, vulvar, or vaginal disease irrespective of HPV type (ie, disease caused by HPV types included and not included in the 9vHPV vaccine) in the modified intention-to-treat population was 14.0 per 1000 person-years in both vaccine groups. In the prespecified per-protocol efficacy population (susceptible population), the incidence of high-grade cervical, vulvar, or vaginal disease related to HPV types 31, 33, 45, 52, and 58 was 0.1 per 1000 person-years in the 9vHPV group and 1.6 per 1000 person-years in the qHPV group; the efficacy of the 9vHPV vaccine was 96.7%, with a 95% confidence interval of 80.9 to 99.8. With respect to immunogenicity, the antibody responses to HPV types 6, 11, 16, and 18 generated by the 9vHPV vaccine were noninferior to those generated by the qHPV vaccine. The frequency of adverse events related to injection site was higher in the 9vHPV group than in the qHPV group. The rate of other adverse events was generally similar in the 2 vaccine groups. In addition to prevention of infection from the 4 HPV types present in the qHPV vaccine, the 9vHPV vaccine prevents persistent infection and disease associated with HPV types 31, 33, 45, 52, and 58 in a susceptible population. The vaccine generated an antibody response to HPV types 6, 11, 16, and 18 that was noninferior to that generated by the qHPV vaccine.